Complex symptomatology among young women who present with stress‐related problems. Issue 2 (21st June 2014) - Strömbäck, Maria; Wiklund, Maria; Salander Renberg, Ellinor; Malmgren‐Olsson, Eva‐Britt
<x xml:space="preserve">Abstract</x> Introduction In Scandinavia and globally, mental health and stress‐related problems among adolescent girls and young women are public health concerns that need attention. The aim of this study was to investigate mental health and somatic symptoms with a special focus on internalised problems, self‐image and body‐mind aspects of body perception in a group of adolescent girls and young women presenting with stress‐related problems at a youth‐friendly Swedish health centre, and to compare them with normative and clinical reference groups. Methods The participants were 47 adolescent girls and young women, aged 17–25 years. The adult self‐report (ASR), social analysis of social behaviour (SASB) and body perception questionnaire (BPQ) were used to measure multiple symptom areas. Results Compared to reference groups, adolescent girls and young women report complex symptomatology with high levels of internalised problems such as anxiousness, depression and somatic complaints. This manifested in attention problems, negative self‐image and perceived bodily discomfort and distrust. Conclusion Adolescent girls and young women emerging into adulthood present complex symptomatology of stress‐related problems. This study gathered valuable information about their symptoms when they were seeking help. These young women showed higher symptom frequency than normative groups, and similar or higher symptom frequency than other clinical groups. Our findings of internalised and cognitive problems, including impaired self‐image and body perceptions, point to the need for preventive strategies and tailored multidisciplinary interventions involving body‐based methods to meet this complexity. Using tenets of stress theory, the complex symptomatology may be understood as logical responses to overwhelming stimuli and demands that exceed their ability to cope and disturb their 'equilibrium'. However, the complex gendered interplays between various external/internal stressors and a broad range of stress responses and health outcomes need further study in a long‐term perspective.